Integrated weed management in grasslands - Schaffner, Urs (Burleigh Dodds Series in Agricultural Science, 2022)
This chapter describes the current status of IWM for grasslands. Its focus is on management practices available to influence transitions in a weed's life cycle: from the soil seed bank to seedling establishment, from the seedling stage to the mature plant, and from the mature plant to the soil seed bank. We provide a conceptual approach to illustrate how management practices available in IWM affect different transitions and then discuss case studies to illustrate how weed management practices have been integrated. The chapter ends with an outlook for further improving IWM in grasslands, especially also under climate change, and for promoting its application.